Sistem Informasi Kepegawaian Dinas Perhubungan Kota Jayapura - Jeanet Damariska Simatauw; Yosefin Caltrin Odelia; Rahmat Haryadi Kiswanto (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The Personnel Information System at the Jayapura City Transportation Office aims to increase efficiency and effectiveness in managing personnel data. In today's digital era, manual data management has limitations that affect the speed and accuracy of information. Therefore, a computerized information system is necessary for better management of employee data. This study aims to analyze the implementation of the personnel information system at the Jayapura City Transportation Office, as well as evaluate its impact on personnel administration performance. The methods used in this study include direct observation of the system in use, interviews with staff and system managers, and analysis of the system's effectiveness in improving data management. The system was evaluated in terms of its ability to streamline administrative tasks, facilitate easy access to personnel data, and enhance overall efficiency in managing personnel information. The results of the study indicate that the system has successfully optimized employee data management, improved administrative efficiency, and made access to information faster and more accurate. However, some obstacles were identified, such as the need for further training for staff to use the system optimally and occasional technical issues with system integration. Despite these challenges, the personnel information system has proven to be an essential tool for improving the overall performance of the personnel administration at the Jayapura City Transportation Office. The study concludes with recommendations for further system enhancements and the importance of ongoing staff training to ensure the system's continued success.